2001
DOI: 10.1042/0264-6021:3590265
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of heparin pentasaccharide bound to antithrombin III

Abstract: The interaction, in aqueous solution, of the synthetic pentasaccharide AGA*IA(M) (GlcN,6-SO(3)alpha 1-4GlcA beta 1-4GlcN,3,6-SO(3)alpha 1-4IdoA,2-SO(3)alpha 1-4GlcN,6-SO(3)alpha OMe; where GlcN,6-SO(3) is 2-deoxy-2-sulphamino-alpha-D-glucopyranosyl 6-sulphate, IdoA is l-iduronic acid and IdoA2-SO(3) is L-iduronic acid 2-sulphate), which exactly reproduces the structure of the specific binding sequence of heparin and heparan sulphate for antithrombin III, has been studied by NMR. In the presence of antithrombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
90
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 29 publications
6
90
1
1
Order By: Relevance
“…A significant enhancement of H5-H2/H5-H4 NOE ratio of the I residue was observed for both OCTA-2 and OCTA-4. This indicates that the conformation of such moiety is driven toward the 2 S O form by the presence of AT, as observed in all AGA*IAcontaining oligosaccharides so far described (10,12,15). In contrast, the IЉ residue of OCTA-2 does not show an H5-H2 tr-NOE signal, indicating that IЉ maintains its 1 C 4 conformation in the presence of AT.…”
Section: Table 2 Equilibrium Dissociation Constant For the Various Olmentioning
confidence: 73%
See 4 more Smart Citations
“…A significant enhancement of H5-H2/H5-H4 NOE ratio of the I residue was observed for both OCTA-2 and OCTA-4. This indicates that the conformation of such moiety is driven toward the 2 S O form by the presence of AT, as observed in all AGA*IAcontaining oligosaccharides so far described (10,12,15). In contrast, the IЉ residue of OCTA-2 does not show an H5-H2 tr-NOE signal, indicating that IЉ maintains its 1 C 4 conformation in the presence of AT.…”
Section: Table 2 Equilibrium Dissociation Constant For the Various Olmentioning
confidence: 73%
“…Despite the strong evidence accumulated on the specificity of heparin-AT binding, (3,10,15), recent studies suggested other possible assemblies between the negatively charged heparin chains and AT (38,39). In these latter studies, the possibility has been considered that sulfated residues in heparin sequences, different from that of the AT-binding site, may activate AT through nonspecific interactions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations